The welfare of immigrants: Resilience and sense of community. Issue 4 (2nd October 2022) - Novara, Cinzia; Scaffidi Abbate, Costanza; Garro, Maria; Lavanco, Gioacchino
Abstract: The accessibility to national health services by immigrants residing in our country has produced a widespread improvement of health indicators and health prevention for the entire population. The main goal of this study is to investigate the welfare conditions of immigrants, alongside two fundamental sources of psychological resources. In particular, the role of resilience and sense of community as protective factors against the risk of developing negative welfare outcomes, including life satisfaction and the perception of general health (physical and mental), were considered as indicators. The following self-report questionnaires were sent to a sample of 354 immigrants, stratified by ethnicity and gender: Life Satisfaction Scale (SWLS), General Health Questionnaire, CD-RISC 10 Scale, and the Sense of Community Index SCI-2 . The results obtained through regression models show how resilience and a sense of community are significant protective factors in terms of life satisfaction and general health. From an applicative point of view, it is highlighted that public and political bodies take a leading role in the design of public health interventions; in fact, their intervention should be aimed at increasing the psychological resources and ability to fulfill the health needs of specific populations.